A novel route to 1, 4-disubstituted-1, 2, 3-triazoles through metal-free decarboxylative azide-alkene cycloaddition. (9th November 2021) - Rengasamy, R.; Vijayalakshmi, K.; Punitha, N.; Paul Raj, J.; Karthikeyan, K.; Elangovan, J.
Graphical abstract: Abstract: A collection of 1, 4-disubstituted 1, 2, 3-triazoles was achieved by decarboxylative [3 + 2] cycloaddition of organic azides and cinnamic acids. Metal-free condition, high regioselectivity and easy accessibility of starting materials are the salient attributes of this protocol.